2009
DOI: 10.1111/j.1467-6494.2009.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Psychological Well‐Being and Resilience by Psychotherapeutic Methods

Abstract: A specific psychotherapeutic strategy for increasing psychological well-being and resilience, well-being therapy, has been developed and validated in a number of randomized controlled trials. The findings indicate that flourishing and resilience can be promoted by specific interventions leading to a positive evaluation of one's self, a sense of continued growth and development, the belief that life is purposeful and meaningful, the possession of quality relations with others, the capacity to manage effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
195
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(215 citation statements)
references
References 80 publications
3
195
0
14
Order By: Relevance
“…The relationship between PWB and generalized anxiety symptoms can be explained by the buffering hypothesis. PWB has been shown to enhance resilience in the context of the prevention of emotional disorders (Fava and Tomba 2009;Johnson et al 2011;Sagone and De Caroli 2014). Resilience refers to a set of attributes and resources that prevent illness following adverse circumstances in the general population and prevent relapse after symptomatic remission in a clinical population (Fava and Tomba 2009).…”
Section: Pwb As Resilience To Anxiety Symptoms: the Buffering Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between PWB and generalized anxiety symptoms can be explained by the buffering hypothesis. PWB has been shown to enhance resilience in the context of the prevention of emotional disorders (Fava and Tomba 2009;Johnson et al 2011;Sagone and De Caroli 2014). Resilience refers to a set of attributes and resources that prevent illness following adverse circumstances in the general population and prevent relapse after symptomatic remission in a clinical population (Fava and Tomba 2009).…”
Section: Pwb As Resilience To Anxiety Symptoms: the Buffering Hypothesismentioning
confidence: 99%
“…PWB has been shown to enhance resilience in the context of the prevention of emotional disorders (Fava and Tomba 2009;Johnson et al 2011;Sagone and De Caroli 2014). Resilience refers to a set of attributes and resources that prevent illness following adverse circumstances in the general population and prevent relapse after symptomatic remission in a clinical population (Fava and Tomba 2009). Adverse circumstances include both poor external environments and individual characteristics including negative emotion, and, cognitive or behavioral predisposition (e.g., neuroticism, ruminative response style, or behavioral inhibition) (Johnson et al 2011).…”
Section: Pwb As Resilience To Anxiety Symptoms: the Buffering Hypothesismentioning
confidence: 99%
“…Additionally, a study that examined gene transcriptional profiles found that eudaimonic well-being (an overarching umbrella term that includes purpose) was associated with enhanced expression of antiviral response genes and reduced expression of proinflammatory genes (31). Furthermore, and perhaps most importantly, purpose-along with other components of psychological well-being-have become the focus of multiple intervention studies designed to improve a person's life outlook (10,(32)(33)(34)(35). Therefore, it may provide a point of intervention for improving health outcomes.…”
mentioning
confidence: 99%
“…An example of a promising intervention is a type of cognitive behavioral approach called Well-Being Therapy. The technique has been shown to effectively help people suffering from a wide range of psychological disorders to achieve optimal levels of psychological well-being (34,35). The technique is typically used after standard care (e.g., cognitive behavioral therapy and pharmacotherapy) and is known to help prevent relapse.…”
mentioning
confidence: 99%
“…Posteriorly revised, the number of items was reduced, and it was renamed as the Oxford Happiness Questionnaire (Hills, & Argyle, 2002). Other measures have been developed, like the Ryff Scales of Psychological Well-Being (Ryff, 1989), which was also reviewed, reduced (Abbott, Ploubidis, Huppert, Kuh, & Croudace, 2010) and converted in an interview format (Fava, & Tomba, 2009), or the Subjective Happiness Scale (Lyubomirsky, & Lepper, 1999).…”
Section: Introductionmentioning
confidence: 99%